Expression as the origin of culture in Eduardo Nicol's thought - Monfort Prades, Juan Manuel (Anales del Seminario de Historia de la Filosofía, 2026)
Throughout this paper an approach to Eduardo Nicol's concept of «expression» in relation to «culture» is exposed. The starting point is the confluence of the three main guiding lines of his thought: metaphysics, dialectic and phenomenology, which led Nicol to establish «expression» as the center of all his thought. In The Human Vocation, Metaphysics of Expression or Critique of Symbolic Reason using figures such as the mystic, the artist, the poet and the philosopher, different perspectives on expression are displayed that come together in a concept of culture as an expression of the same human being.
Keywords: being; community; culture; expression; metaphysics